The psychometric properties of "Hospital Survey on Patient Safety Culture" in Czech enviroment - Daniela Bartoníčková; Dominika Kalánková; Zdeňka Mikšová; Radka Kurucová; Šárka Tomová; Katarína Žiaková (University of Ostrava, 2019)
Aim: To analyze the psychometric properties of the Hospital Survey on Patient Safety Culture (HSOPS) in internal care units at a specific teaching hospital in the Czech Republic. Design: The paper has the character of a cross-sectional validation study. Methods: The study was conducted between November 2015 and January 2016. The convenience sample consisted of 207 registered nurses working in internal care units at a specific faculty hospital in the Czech Republic. Analysis of the psychometric properties of the HSOPS was conducted using Principal Component Analysis (PCA) and reliability testing. Results: Acceptable psychometric properties of the HSOPS were verified in our study. We confirmed 12 components of the HSOPS, the same number stated in the original version from the Agency for Healthcare Research and Quality (AHRQ). The reliability of the instrument was evaluated using the Cronbach alpha coefficient, and is considered acceptable. Conclusion: These findings can help healthcare institutions to raise awareness of patient safety culture and to gain a comprehensive overview of the individual dimensions of patient safety culture. In the future, the instrument could help to compare the components of patient safety culture, not only at a national but also at an international level.